The Influence of Brand Equity, Service Quality, and Organizational Commitment on Job Loyalty and Lecturer Performance - haeruddin; Ibrahim; Asriati; Iqbal AR (Jurnal Manajemen Indonesia, 2025)
This study aims to examine the influence of brand equity, service quality, and organizational commitment on lecturer performance through job loyalty at Universitas Muhammadiyah Makassar. Employing a descriptive quantitative research approach, data were collected from 106 respondents via questionnaires. Hypotheses were tested using Path Analysis and Sobel Test methods. The research findings reveal that brand equity has a positive but non significant effect on job loyalty, while service quality and organizational commitment significantly influence job loyalty. Additionally, brand equity, service quality, organizational commitment, and job loyalty collectively have a positive and significant impact on lecturer performance. Interestingly, brand equity does not significantly affect lecturer performance through job loyalty; however, service quality and organizational commitment significantly influence lecturer performance through job loyalty. Based on these findings, recommendations are provided to the university management to develop holistic and integrated strategies aimed at enhancing service quality, reinforcing organizational commitment, and improving lecturer job loyalty. These strategies may include professional development programs, infrastructure and facility enhancements, fostering an inclusive organizational culture, and strengthening communication and relationships between management and lecturers. Furthermore, efforts to enhance institutional branding are suggested to bolster the university's image and reputation as a leading academic institution committed to quality education